Wild birds bred in captivity in the city of Eirunepé, middle Juruá river, southwestern Brazilian Amazonia - de Oliveira, Miberly Cavalcante; Pedroza, Diego (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
In this study, we conducted a survey of captive wild birds and the way to raise and keep these animals in the city of Eirunepé, Amazonas, Brazil. We used two data collection methods: a random selection of streets to be sampled and a number of breeders indicated by informants. We registered 142 birds belonging to 15 species of Psittacidae, Rallidae, and Thraupidae. The three species with the highest percentages of registrations were Sporophila angolensis (34.5%, n = 49), S. lineola (33.8%, n = 48), and Amazona festiva (9.2%, n = 13). The raising methods observed were: cages (84.51%, n = 120), released in the vicinity of residence (9.15%, n = 13), and tied at the tarsus (6.34%, n = 9). Of the registered species, only S. cf. maximiliani is critically endangered with extinction. We conclude that the keeping of captive birds in Eirunepé is largely restricted to passerines and that they are raised as pets, for singing and fighting contests or rehabilitation. Furthermore, different kinds of birdkeeping may vary according to the size of individuals. It is essential that breeders have knowledge about the proper ways of breeding and how to obtain wild birds legally in Brazil.